Mr. Putter & Tabby smell the roses - Rylant, Cynthia (Rylant, Cynthia. Mr. Putter and Tabby., 2015)
When Mr. Putter and Tabby take Mrs. Teaberry to the Conservatory for her birthday, Zeke tries his best to stay out of trouble, but one of the trees is irresistible.